Application of work function measurements in the study of surface catalyzed reactions on Rh(1 0 0). (2nd January 2018) - Caglar, Basar; Kizilkaya, Ali Can; Niemantsverdriet, J. W. (Hans); Weststrate, C. J. (Kees-Jan)
Abstract: The present article aims to show how work function measurements (WF) can be applied in the study of elementary surface reaction steps on metallic single crystal surfaces. The work function itself can in many cases not be interpreted directly, as it lacks direct information on structural and chemical nature of the surface and adsorbates, but it can be a powerful tool when used together with other surface science techniques which provide information on the chemical nature of the adsorbed species. We here, illustrate the usefulness of work function measurements using Rh(100) as our model catalyst. The examples presented include work function measurements during adsorption, surface reaction, and desorption of a variety of molecules relevant for heterogeneous catalysis. Surface coverage of adsorbates, isosteric heat of adsorption, and kinetic parameters for desorption, desorption/decomposition temperatures of surface species, different reaction regimes were determined by WF with the aid of other surface science techniques. Abstract :